Blasticidin-S deaminase, a new selection marker for genetic transformation of the diatom Phaeodactylum tricornutum - Jochen M. Buck; Carolina Río Bártulos; Ansgar Gruber; Peter G. Kroth (PeerJ, 2018)
Most genetic transformation protocols for the model diatom Phaeodactylum tricornutum rely on one of two available antibiotics as selection markers: Zeocin (a formulation of phleomycin D1) or nourseothricin. This limits the number of possible consecutive genetic transformations that can be performed. In order to expand the biotechnological possibilities for P. tricornutum, we searched for additional antibiotics and corresponding resistance genes that might be suitable for use with this diatom. Among the three different antibiotics tested in this study, blasticidin-S and tunicamycin turned out to be lethal to wild-type cells at low concentrations, while voriconazole had no detectable effect on P. tricornutum. Testing the respective resistance genes, we found that the blasticidin-S deaminase gene (bsr) effectively conferred resistance against blasticidin-S to P. tricornutum. Furthermore, we could show that expression of bsr did not lead to cross-resistances against Zeocin or nourseothricin, and that genetically transformed cell lines with resistance against Zeocin or nourseothricin were not resistant against blasticidin-S. In a proof of concept, we also successfully generated double resistant (against blasticidin-S and nourseothricin) P. tricornutum cell lines by co-delivering the bsr vector with a vector conferring nourseothricin resistance to wild-type cells.